Knowledge Assessment on Foot Reflexology as a Non-Pharmacological Pain Management Strategy among Post-Operative LSCS Mothers (International Journal of Environmental Sciences, 2025)
Introduction: Caesarean section is a surgical procedure often carried out to protect the health and lives of both mother and baby. A major issue faced by women-in post-LSCS is pain. Foot reflexology is a complementary therapy known for being safe, simple, non-invasive, and effective in managing pain.Methodology: The study adopted a non-experimental, descriptive research design. It was conducted at Swamy Vivekanandha Medical College Hospital and Research Institute, Namakkal District. Using purposive sampling, 60 post-LSCS mothers were selected. A structured questionnaire was employed to assess their knowledge regarding the effectiveness of foot reflexology in pain management.Results: Findings revealed that 42 participants (70%) had inadequate knowledge, 18 (30%) had moderate knowledge, and none demonstrated adequate knowledge about the use of foot reflexology for post-LSCS pain. Discussion: The discussion is based on data analysed using descriptive and inferential statistics. The study’s objectives guided the interpretation. Chi-square analysis revealed a significant relationship between knowledge levels and variables such as education and occupation at the 5% level. However, other variables including age, religion, and family income, type of family, place of residence, pregnancy history, and number of children were not statistically significant. Conclusion: Overall, mothers' knowledge regarding the use of foot reflexology for pain relief following LSCS is lacking. It is essential for healthcare professionals to take steps to enhance awareness and understanding of this pain management technique.